GIS-Based Shallow Groundwater Potential Zone Assessment Using ALOS AVNIR-2 Remote Sensing Data (Case Study: Bedog Sub-Watershed, Yogyakarta) - Lesan; Dian; Supang (Remote Sensing Technology Study Program, 2025)
This research aimed to determine how effective the integration of remotely sensed data of ALOS - AVNIR 2 and Geographic Information System (GIS) to assess the shallow groundwater potential zone in Bedog Sub Watershed and spatial analysis of potential groundwater produced in the form of a map. Primary data used is the image of ALOS - AVNIR 2 supported by some thematic maps and other data. The method used is integrate the remote sensing techniques and GIS by buildup shallow groundwater potential zone map in Bedog sub watershed with parametric approach (for the origin of volcanic landforms with sand aquifer material). For potential groundwater contained in landforms from solusional processes, the method used is the measurement of groundwater potential in the field with quantitative descriptive approach. The accuracy of interpretation from each parameter are for parameter of soil texture resulting 75 % of accuracy, 77.78% of slope and 85% of land cover. Shallow groundwater potential maps generated from the origin of volcanic landforms with material aquifer of sands produces shallow groundwater potential in 3 classes (low potential, moderate potential and high potential) through the measurement of sahllow groundwater level information in the field. It is able to be generalized to information of aquifer formation that contain of it. Shallow groundwater potential in landforms from solusional processes with a limestone rock as a material shows very varied potential shallow groundwater which have been seen from differences phenomenon in the field. Keywords : Remotely sensed data of ALOS - AVNIR 2, GIS, terrain parameters, shallow groundwater potential